A Comparison of Readability in Science-Based Texts: Implications for Elementary Teachers - Gallagher, Tiffany L.; Fazio, Xavier; Ciampa, Katia (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
Science curriculum standards were mapped onto various texts (literacy readers, trade books, online articles). Statistical analyses highlighted the inconsistencies among readability formulae for Grades 2–6 levels of the standards. There was a lack of correlation among the readability measures, and also when comparing different text sources. Online texts were the most disparate with respect to text difficulty. These findings suggest implications for elementary teachers to support students who learn through reading online, science-based resources. As 21st-century learning through multi-modal literacies evolves, the readability of online, content-based text should be evaluated to ensure accessibility to all readers.